2016
DOI: 10.1038/srep23287
|View full text |Cite
|
Sign up to set email alerts
|

Unfractionated bone marrow cells attenuate paraquat-induced glomerular injury and acute renal failure by modulating the inflammatory response

Abstract: The aim of this study was to evaluate the efficacy of unfractionated bone marrow cells (BMCs) in attenuating acute kidney injury (AKI) induced by paraquat (PQ) in a mouse model. PQ (55 mg/kg BW) was intraperitoneally injected into C57BL/6 female mice to induce AKI, including renal function failure, glomerular damage and renal tubule injury. Glomerular podocytes were the first target damaged by PQ, which led to glomerular injury. Upon immunofluorescence staining, podocytes depletion was validated and accompanie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…These two parameters are biomarkers of renal toxicity [33] and the increase indicate renal damage associated with increased urea production. This is in line with previous reports [34,35]. However, garlic supplementation showed the significant ameliorative potential to the abnormal urea and creatinine production as presented by rats in the garlic group.…”
Section: Discussionsupporting
confidence: 93%
“…These two parameters are biomarkers of renal toxicity [33] and the increase indicate renal damage associated with increased urea production. This is in line with previous reports [34,35]. However, garlic supplementation showed the significant ameliorative potential to the abnormal urea and creatinine production as presented by rats in the garlic group.…”
Section: Discussionsupporting
confidence: 93%
“…Urea and Cr are among the markers of renal toxicity workup (29). In this study, there is an increase in serum urea and Cr levels in group 2 (Table 1), which indicates the paraquat-induced renal damage; which was consistent with previous studies (27,29,30). In our study, administration of silymarin led to protect kidneys against paraquat toxicity and reduces serum urea and Cr levels ( Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…Paraquat is secreted by proximal tubules before renal damage, but tubular damages happen with an increase in paraquat concentration. In paraquat-induced renal toxicity, primarily the glomerular coatings (podocytes) are damaged; then, tubular degeneration, and the formation of eosinophilic granular cytoplasm is happen in distal and proximal tubules (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α also activates caspase-mediated apoptosis through activation of the death receptor pathway 55 . It was reported that TNF-α and IL-6 expression were significantly elevated in chronic renal failure patients 60 and rat AKI models using cisplatin and paraquat to induce AKI 61 , 62 . MCP-1 is a more recently studied renal biomarker which is expressed in injury and inflammation sites and directs the recruitment of macrophages, which bind to chemokine receptors to promote macrophage adhesion and chemotaxis 63 .…”
Section: Discussionmentioning
confidence: 99%